Tadao Ando : houses - Jodidio, Philip, ....- (New York : Rizzoli, 2013)
The most comprehensive collection of residential projects from the world's most internationally recognized and renowned architect.\nAndo's structures are immensely practical and habitable as well as rigourous and dynamic, often seeming to have evolved naturally out of the surrounding environment to shelter their inhabitants -serving as living spaces in both senses of the word. This exhausitive study of his residentail work includes striking color photographs as well as detailed architectural drawings and plans of more than thirty years of Ando's residential work, from the Sumiyoshi Row House in 1975 to the current houses for such design connaisseurs as Karl Lagerfeld and Tom Ford.
Keywords: Ando, Tadao